Some Families of Bilinear and Bilateral Generating Functions in Function Spaces Associated with Hypergeometric Polynomials - Yashwant Jaiswal , S. K. Sahani , A. K. Thakur (Mathematical Statistician and Engineering Applications, 2022)
In this research paper we have obtained some specific theorems which one then applied to obtain a set of bilinear and bilateral generating functions in function spaces in terms of Laplace, beta and some other integrals. These theorems include as special cases many known results of the authors [1].